Association between Adipokines and Coronary Artery Lesions in Children with Kawasaki Disease - Kim, Hyun Jung (The Korean Academy of Medical Sciences, 2014)
Body fat is an important source of adipokine, which is associated with energy balance and inflammatory and immune responses. However, the role of adipokines in coronary artery complications in Kawasaki disease (KD) has not yet been fully explained. We investigated whether serum adipokine level can be a useful marker for patients with KD who are at higher risk of developing coronary artery lesion (CAL). We measured adipokine levels and other inflammatory parameters in 40 patients with KD, 32 febrile controls, and 15 afebrile controls. Interleukin (IL)-6, tumor necrosis factor (TNF)-α and other laboratory parameters were also measured before and after intravenous immunoglobulin therapy, and in the convalescent phase. At admission, the serum resistin levels in KD children were significantly higher than those in controls (177.56 ng/mL in KD children, 76.48 ng/mL in febrile controls, and 17.95 ng/mL in afebrile controls). In patients with KD, resistin levels were significantly associated with decreased hemoglobin levels (P=0.049) and increased IL-6 levels (P=0.014). The serum IL-6 levels were significantly higher and body mass index was significantly lower in the group of KD with CALs than those without CALs (228.26 ng/mL vs. 39.18 ng/mL and 15.09 vs. 16.60, respectively). In conclusion, resistin is significantly elevated in KD patients, although it has no prognostic value of predicting coronary artery lesion in the acute stage. GRAPHICAL ABSTRACT: [Image: see text]